Biofilm formation in invasive Staphylococcus aureus isolates is associated with the clonal lineage. (January 2016) - Naicker, Preneshni R.; Karayem, Karayem; Hoek, Kim G.P.; Harvey, Justin; Wasserman, Elizabeth
Abstract: The contribution of the genetic background of Staphylococcus aureus to biofilm formation is poorly understood. We investigated the association between the genetic background and the biofilm forming ability of clinical invasive S. aureus isolates. Secondary objectives included investigating any correlation with biofilm formation and methicillin resistance or the source of bacteraemia. The study was conducted at a 1300-bed tertiary hospital in Cape Town, South Africa. S. aureus isolates obtained from blood cultures between January 2010 and January 2012 were included. Genotypic characterization was performed by PFGE, spa typing, SCC mec typing and MLST. Thirty genotypically unique strains were assessed for phenotypic biofilm formation with the microtitre plate assay. All isolates were tested in triplicate and an average optical density, measured at a wavelength of 490 nm, was determined. The biofilm forming ability of isolates with A490 ≤ 0.17 were considered non-adherent, A490 > 0.17 'weak positive' and A490 > 0.34 'strong positive'. Fifty seven percent of isolates formed biofilms. Weak biofilm formation occurred in 40% (n = 12) and strong biofilm formation in 17% (n = 5) of isolates. All 5 isolates capable of strong biofilm formation belong to one spa clonal complex ( spa -CC 064). Strains from spa -CC 064 were capable of higher biofilm formation than other spa clonal complexes (p = 0.00002). These 5 strains belonged to MLST CC5 and CC8. Biofilm formation correlates with the spa clonal lineage in our population of invasive S. aureus strains. Biofilm formation did not correlate with methicillin resistance and was not related to the source of bacteraemia.